Membrane Cholesterol in Skeletal Muscle: A Novel Player in Excitation-Contraction Coupling and Insulin Resistance. (6th March 2017) - Barrientos, G.; Sánchez-Aguilera, P.; Jaimovich, E.; Hidalgo, C.; Llanos, P.
Abstract : Membrane cholesterol is critical for signaling processes in a variety of tissues. We will address here current evidence supporting an emerging role of cholesterol on excitation-contraction coupling and glucose transport in skeletal muscle. We have centered our review on the transverse tubule system, a complex network of narrow plasma membrane invaginations that propagate membrane depolarization into the fiber interior and allow nutrient delivery into the fibers. We will discuss current evidence showing that transverse tubule membranes have remarkably high cholesterol levels and we will address how modifications of cholesterol content influence excitation-contraction coupling. In addition, we will discuss how membrane cholesterol levels affect glucose transport by modulating the insertion into the membrane of the main insulin-sensitive glucose transporter GLUT4. Finally, we will address how the increased membrane cholesterol levels displayed by obese animals, which also present insulin resistance, affect these two particular skeletal muscle functions.